Применение магнитной жидкости с фазовым переходом в погружных электромеханических преобразователях - Заблодский, Николай Николаевич; Грицюк, Владимир Юрьевич; Клендий, Петр Богданович; Сорокин, Дмитрий Сергеевич (НТУ "ХПИ", 2018)
Приведены результаты математического моделирования взаимосвязанных электромагнитных и тепловых процессов в погружных электро-механических преобразователях с магнитожидкостным заполнением. Получены механические характеристики, зависимости распределения магнитной индукции и плотности вихревого тока в активной части погружного преобразователя. Применение магнитной жидкости в электромеханических преобразователях позволит обеспечить увеличение электромагнитного момента на 8-10 % за счет снижения магнитного сопротивления воздушного зазора, а также улучшить условия теплообмена с окружающей средой.

Results of mathematical modeling of interrelated electromagnetic and thermal processes in submersible electromechanical converters with magneto-liquid filling are presented. A number of modifications of submersible electromechanical transducers are performed with the filling of the internal volume with a magnetic fluid serving simultaneously as a sealant agent and a refrigerant. Mechanical characteristics are obtained, th e dependences of the distribution of magnetic induction and the density of the eddy current in the active part of the submerged converter. The use of a magnetic fluid in electromechanical converters will provide an increase in the electromagnetic torque by 8-10 % due to a decrease in the magnetic resistance of the air gap, and also improve the conditions for heat exchange with the surrounding medium.
A magnetic fluid application with a phase transition in a submersible electromechanical converters
Keywords: магнитожидкостное заполнение; массивный ротор; конечно-элементная модель; магнитная индукция; электромагнитный момент; electromechanical converter; magnetic-fluid filling; massive rotor; finite element model; magnetic induction; electromagnetic torque